Circulating interleukin‐6 as a biomarker in a randomized controlled trial of modified‐release prednisone vs immediate‐release prednisolone, in newly diagnosed patients with giant cell arteritis. (17th September 2019) - Miler, Emma; Stapleton, Philip P.; Mapplebeck, Sarah; Mackerness, Craig; Gayford, Dawn; Aung, Tin; Wilson, Lisa; Schofield, Paul; Dasgupta, Bhaskar
Abstract: Objectives: To measure serial interleukin (IL)‐6 levels in newly diagnosed patients with giant cell arteritis (GCA), treated in a randomized controlled trial of modified‐release prednisone (MR) vs immediate‐release prednisolone (IR) used in a tapering regimen conforming to British Society for Rheumatology GCA guidelines. Methods: Patients (n = 12) were randomized into 2 treatment arms (7 MR, 5 IR) and followed over 26 weeks. We measured IL‐6 with additional markers. Results: A significantly higher overall mean IL‐6 level ( P  < .05) was seen in IR (mean = 12.15, standard error [SE] = 1.90) compared with MR (mean = 4.39, SE = 1.84). Mean collagen type 1 cross‐linked C‐telopeptide (CTX) concentration was significantly higher ( P < .05) in both groups at week 4 (mean = 0.29, SE = 0.04) compared with week 26 (mean = 0.13, SE = 0.02). MR patients had adrenocorticotropic hormone (ACTH) suppression compared with IR ( P  < .05) throughout without differences in cortisol levels ( P  = .34). No significant differences were seen between arms in other markers. Conclusion: Our study suggests that elevated levels of IL‐6 in new GCA are better suppressed by MR prednisone compared with IR prednisolone. CTX was significantly reduced in both treatment arms indicating early metabolic effect of glucocorticoids on bone. ACTH suppression with MR prednisone may reflect a greater impact on the hypothalamic‐pituitary‐adrenal axis although cortisol was not affected. MR prednisone warrants further investigation in GCA.